Study on plant regeneration from embryo of a group indica and japonica varieties of Vietnamese rice for transformation approach - Quyen, Cao Le; Hoan, Le Kim; Ham, Le Huy; Hoi, Pham Xuan (Academia Journal of Biology, 2014)
Although, a highly efficient gene transfer method mediated by Agrobacterium tumefaciens was developed for both Japonica and Indica rice. However, highly efficient transformation apporoach is now facing with difficulty in in vitro system as there are not many tissue culture protocols for different Vietnamese rice varieties. Here, we report the callus forming potency and plant regeneration capacity of 59 vietnamese rice varieties including 26 common varieties, 27 droupt resistance varieties and 6 high quality varieties. At least, 32 rice varieties in a total of 59 surveyed varieties have callus forming potency. Among them, 19 rice varieties have callus formation rate of 40 - 60%, a variety has callus formation rate of 71% and two varieties have callus formation rate of above 90%. The 1xMS medium supplementented with a range of 1.5-2 mg/l 2,4D seem to be optimal for callus forming. All 32 calus forming rice varieties showed plant regeneration capacity. Out of wich, 24 rice varieties have regeneration score above 60%, specially three rice varieties have regeneration score of above 80%. The 1xMS medium supplementented with 2mg/l BAP, 0.5 mg/l kinetine, 0.1mg/l casein seem to be optimal for plant regeneration. The result is opening a posibility for transformation protocol development for Vietnamese rice varieties.